CRIDA 18R, a new horsegram (Macrotyloma uniflorum) variety: germination as influenced by higher CO2, temperature and relative humidity - Reddy, P Raghu Ram; Maruthi, V; Vanaja, M; Reddy, B M K; Jainender, Jainender; Archana, G; Razak, S K Abdul; Maheswari, M; Venkateswarlu, B (The Indian Journal of Agricultural Sciences, 2012)
The better response of horsegram germination percentage to elevated CO2 is a positive indication as this particular crop being thermo and photo-sensitive in nature at ambient field level. The higher concentration of CO2 may play ameliorating role to offset the negative effects of variable temperature and relative humidity under climatic change scenario.